The Effective Difference Application of Chitosan Gel with Different Molecular Weight and Aloe vera on The Density of Collagen Fibers in Wound Healing of Traumatic Ulcer - Michelle Suhartono; Sularsih; Nafi’ah (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: Traumatic ulcer is one of the most common oral wounds. Chitosan has mucoadhesive characteristic while Aloe vera containing lignin which is able to penetrate the skin. It is expected that the combined gel of chitosan and Aloe vera will function as wound healing accelerator in traumatic ulcer. Molecular weight is one of the characteristics of chitosan quality. Purpose: the aim of this experiment was to know the density of collagen fibers in wound healing of traumatic ulcer using the combined gel of chitosan with different molecular weight and Aloe vera. Materials and Methods: 30 Male Rattus Norvegicus were divided into 3 groups. Group I was control group (without chitosan and Aloe vera), group II was given low molecular weight chitosan and Aloe vera, group III was given high molecular weight chitosan and Aloe vera. The groups were given traumatic ulcer making with 4 mm diameter and 2 mm depth. Rats were sacrificed by decapitation on day 3 and 7 then they were examined histopatologically to see the density of collagen fibers. Result: Statistical analysis with Kruskall Wallis and Mann-Whitney U test showed that there were significant difference p<0,05 between high and low molecular weight chitosan with Aloe vera group on day 3 and 7. Conclusion: Chitosan with high molecular weight and Aloe vera were more effective in wound healing of traumatic ulcer because they increase the density of collagen fibers.